Does Internet Connect to Social Justice Perception in China? - Zhou, Dong; Zhu, Jinyu; Guo, Yihan (Frontiers in Psychology, 2022)
The world has witnessed an important and dramatic transition during the past decades, social and economic challenges related to the advancement of digital technologies. Meanwhile, inequalities of distributions of resources and opportunities obstinately exist in around the world. This current study innovates by utilizing household survey datasets to empirically evaluate the impact of Internet utilization on individual’s perception towards social justice in China. Estimates suggest that Internet utilization generates a significant negative effect on perceived social justice (in general, -5%). In China, there are 1.032 billion internet users by the end of 2021, accounting for 73% of the total population. It suggests that 3.65% of the population, around 5 million people, might consider the current society is injustice if all circumstances keep unchanged. For robustness checks, we not only run multivariate regressions, implement different model specification and use alternative measures as well as datasets, but also approach instrumental variable estimation with regional rainfall for causal inference. Consistent conclusions are found. Also, we find stronger negative effects among male, eastern provinces and urban areas samples. To the end, our results shed lights on policy implication, for example, internet associated public interventions can be focused on justice cultivation and information transparency.